2019
DOI: 10.3991/ijim.v13i02.9941
|View full text |Cite
|
Sign up to set email alerts
|

Learning Media Repository and Delivery System for Smart Classroom using IoT and Mobile Technologies

Abstract: <span>This paper presents a learning media repository and delivery system (LMRD) for a smart classroom using IoT and mobile technologies. It was designed to support active learning pedagogy. Teachers are able to broadcast learning media or course materials directly to the student mobile devices, after that the students can interact to the media by drawing, editing, or adding comments using their mobile device then broadcast it back to present or reflect their thinking. The system includes 1) a server usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Agreeing with this, Mohamed et al (2018) state that IoT can improve the quality of the learning experience that enables realtime insights and performance. Students can visualize and process data uploaded using smartphone devices (Saraubon, 2019). This explanation concludes that the use of media in learning helps students learn about difficult and abstract physics material.…”
Section: Introductionmentioning
confidence: 87%
“…Agreeing with this, Mohamed et al (2018) state that IoT can improve the quality of the learning experience that enables realtime insights and performance. Students can visualize and process data uploaded using smartphone devices (Saraubon, 2019). This explanation concludes that the use of media in learning helps students learn about difficult and abstract physics material.…”
Section: Introductionmentioning
confidence: 87%
“…However, the necessary facilities are internet facilities that can be used to access materials online [18]. Besides, the capabilities of MT also need to be emphasized so that it can support every software and application needed according to current needs [19]. The research hypothesis is as below: H 4 .…”
Section: Facilitating Conditions (Fc)mentioning
confidence: 99%
“…These studies have shown that using the website attributes to shape positive behavior, acquire knowledge, and attempt to find information and enhance academic achievement [13,[29][30][31]. Other findings stated that using the web can stimulate learning motivation, develop literacy, improve student activity, intensify reading apprehension and learning endurance, and increase student engagement [32][33][34][35][36][37][38]. In comparison, another study found that websites reduced student social life [30].…”
Section: Web-based Animation Videomentioning
confidence: 99%